O cogito revisitado - Nina Virgínia de Araújo Leite (Cadernos de Estudos Lingüísticos, 2011)
The present paper aims at discussing the questions related to Linguistics and Cognition from the psychoanalytical perspective, focusing on the notion of a subject of modern science. The strategy for doing this centres on re-visiting the cartesian cogito and demonstrating the linguistic nature of the subjective experience implied in the inauguration of the so called modern science. It demonstrates how the freudian discoveries can be taken as necessary to build a notion of subjectivity compatible to the scientific status of Linguistics.